The skills and knowledge needed for principals in Qatar's independent schools: policy makers', principals' and teachers' perspectives. Issue 6 (2nd November 2019) - Romanowski, Michael H.; Sadiq, Hissa; Abu-Tineh, Abdullah M.; Ndoye, Abdou; Aql, Mofeed
ABSTRACT: Research indicates that principals play a significant role in schools influencing student achievement and teacher effectiveness. This is particularly true in times of educational reform. Qatar has been engaging in a significant educational reform since 2004. This study examines the knowledge and skills needed for effective principals from the perspectives of policy makers, principals and teachers working in Qatar's independent schools. Interviews with 3 policy makers, 21 principals and 82 teachers in focus groups indicated the knowledge and skills needed by principals are already embedded in the National Professional Standards for School Leaders but participants indicated a concern as to the degree these are implemented by principals in Qatar's schools. More importantly, a large majority of all participants specified a need for principals to develop leadership knowledge and skills regarding working with diverse faculty, students and parents. Recommendations based on these findings are provided in order to develop more effective principals in the context of Qatar's independent schools.